Obsessive compulsive disorder phenomenology: forms and contents of obsessions and compulsions in East Turkey - Tezcan, E; Millet, B (Doin Editeurs, 1997)
The aim of our study was to analyse the obsessions and compulsions of patients diagnosed as Obsessive-Compulsive Disorder in terms of their forms and their contents in Eastern Turkey. Forms and contents of 181 obsessions and 164 compulsions found in 108 patients were classified by using the classification system developed by Khanna and Channabasavanna. Dirt and contamination fear was the most common obsessive theme, followed by religion. Washing compulsion content was found in nearly two thirds of the patients then followed by specific activities (praying, counting and touching). Our data was concordant with previous studies except for religious obsessions in particular, second in frequency.
Keywords: compulsion content; disorder; form; obsession; obsessive-compulsive; phenomenology